2020
DOI: 10.1177/1524838020979674
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Stressors and Adolescent Substance Use: A Review of 21st-Century Literature

Abstract: The aim of this review is to assess empirical studies from the last 2 decades that have examined the association between cumulative stressors and adolescent substance use. Cumulative stressors were measured in these studies with adverse childhood experiences or adolescent stressful life events inventories. The 109 articles meeting the eligibility criteria that emerged from the review demonstrated a consistent, yet modest, association between cumulative stressors and adolescent substance use. Of note, several s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 127 publications
0
14
0
Order By: Relevance
“…The link between ACEs and substance misuse was moderated by depressive symptoms, religiosity, future orientation, family cohesion and quality of relationships. Hoffman and Jones 2020 24 PA, SA, EA, N, DV, household SU, household MI, household incarceration, PS SUD, misuse, dependence. General population of adolescents or adolescents from secondary schools.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The link between ACEs and substance misuse was moderated by depressive symptoms, religiosity, future orientation, family cohesion and quality of relationships. Hoffman and Jones 2020 24 PA, SA, EA, N, DV, household SU, household MI, household incarceration, PS SUD, misuse, dependence. General population of adolescents or adolescents from secondary schools.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, Hoffmann and Jones reviewed the literature on cumulative adversities and adolescent substance use, and found evidence of a positive association for initiation, frequency of use, disorder, and dependence. 24 Moreover, among young adults, Rogers et al found that greater ACEs predicted increased quantity and frequency of alcohol consumption, harmful alcohol use, and alcohol use disorder. 31 This was also confirmed for other drugs, with studies finding a positive association between ACEs and tobacco and e-cigarette use, cannabis dependence, other illicit drugs and non-medical prescription opioid use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, scholars have posited that the stress produced by family reconfiguration may lead some youth to substance use as a way of coping with the pressures they feel at home. The euphoria produced by psychoactive substances can furnish a way for young people to alleviate feelings of distress, anxiety, and negative affect due to adverse family experiences and other untoward events [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%